Reappraisal of the extinct seal “Phoca” vitulinoides from the Neogene of the North Sea Basin, with bearing on its geological age, phylogenetic affinities, and locomotion - Dewaele, Leonard; Amson, Eli; Lambert, Olivier; Louwye, Stephen (PeerJ, 2017)
Background Discovered on the southern margin of the North Sea Basin, “Phoca” vitulinoides represents one of the best-known extinct species of Phocidae. However, little attention has been given to the species ever since its original 19th century description. Newly discovered material, including the most complete specimen of fossil Phocidae from the North Sea Basin, prompted the redescription of the species. Also, the type material of “Phoca” vitulinoides is lost. Methods “Phoca” vitulinoides is redescribed. Its phylogenetic position among Phocinae is assessed through phylogenetic analysis. Dinoflagellate cyst biostratigraphy is used to determine and reassess the geological age of the species. Myological descriptions of extant taxa are used to infer muscle attachments, and basic comparative anatomy of the gross morphology and biomechanics are applied to reconstruct locomotion. Results Detailed redescription of “Phoca” vitulinoides indicates relatively little affinities with the genus Phoca, but rather asks for the establishment of a new genus: Nanophoca gen. nov. Hence, “Phoca” vitulinoides is recombined into Nanophoca vitulinoides. This reassignment is confirmed by the phylogenetic analysis, grouping the genus Nanophoca and other extinct phocine taxa as stem phocines. Biostratigraphy and lithostratigraphy expand the known stratigraphic range of N. vitulinoides from the late Langhian to the late Serravallian. The osteological anatomy of N. vitulinoides indicates a relatively strong development of muscles used for fore flipper propulsion and increased flexibility for the hind flipper. Discussion The extended stratigraphic range of N. vitulinoides into the middle Miocene confirms relatively early diversification of Phocinae in the North Atlantic. Morphological features on the fore- and hindlimb of the species point toward an increased use of the fore flipper and greater flexibility of the hind flipper as compared to extant Phocinae, clearly indicating less derived locomotor strategies in this Miocene phocine species. Estimations of the overall body size indicate that N. vitulinoides is much smaller than Pusa, the smallest extant genus of Phocinae (and Phocidae), and than most extinct phocines.
Keywords: Phocidae; Neogene; North Sea Basin; Belgium; Redescription; Taxonomy; Locomotion